The influence of paraproteinaemia on the Technicon automated platelet counter - Hall, P. C. (1974)
In five patients whose serum contained a paraprotein it has been shown that platelet counts obtained using the Technicon AutoCounter are much too high. In two patients with IgG gammopathy the error is caused by some factor in the red cells lysed by the diluent solution 2M urea. In three patients with IgM gammopathy spurious platelet counts were produced by platelet-poor plasma when diluted with 2M urea. It is recommended that at the present time no patient known to have a paraprotein should have platelet counts performed on the AutoCounter.